Inbound Content - Champion, Justin (Ascent Audio, 2019)
Develop and implement an effective content strategy tailored to your business's needs Inbound Content is a step-by-step manual for attracting the right people, turning them into leads, and closing them into customers. Today, everyone knows that content is king. It's how we engage, how we inform, and how we pass the time; content is everywhere, and if you're not leveraging its power to promote your business, you've already been left behind. Having a website and social media is not enough; if you truly want to take advantage of unprecedented levels of connectedness, you have to create content that draws customers in. It's not about blindly expanding reach, it's about reaching out to the right audience. Today's marketplace is no longer about chasing the sale-with the right approach to content, your customers will come to you. Your content must be valuable, relevant, and consistent-but how should it be implemented at the actual content-creation level? This book shows you how to develop a unified strategy, create compelling content tailored to your needs, and utilize that content to its greatest advantage in order to build your brand.
Online resource; Title from title page (viewed October 29, 2019)
Keywords: Business; Affaires; businesses (business enterprises); Audiobooks